The Effectiveness of Career Group Counseling with Modeling Technique to Improve Vocational Identity and Career Decision Making - Marlina, Elin Siti; Sugiyo, Sugiyo; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Vocational identity is a foundation in career decision making. It is a developmental process which covers choosing, entering, and progressing education and occupation. In relation to this, the present study attempted to examine the effectiveness of career group counseling with modeling technique to enhance vocational identity and career decision making of MAN 1 students in Semarang City. It used an experimental method with pretest-posttest control group design by involving 14 students whose vocational identity and career decision making were low until medium as the subjects. Based on Wilcoxon Signed Rank and Mann-Whitney tests, the intervention of group counseling with modeling technique could increase the vocational identity and career decision making of MAN 1 students in Semarang City. Further study implication.